IDENTIFIKASI KEBERHASILAN PENDIDIKAN MASYARAKAT MELALUI PROGRAM PEMBERDAYAAN PEREMPUAN BERBASIS KELOMPOK USAHA BERSAMA - Wayan Tamba; M A Rizka; Mohnan Mohnan (Jurnal Paedagogy, 2017)
The purpose of this study was to determine the level of success of community education through the “Tibu Bedok” Joint Business Group (KUB) women's empowerment program and to find out what factors influence the success of women's empowerment programs through the “Tibu Bedok” Joint Business Group (KUB). Cemare Hamlet, Sheet Village of West Lombok, 2015. The data analysis technique used in this study was to reduce data, then present the data and draw conclusions. The results of this study indicate that the success of community education through the women's empowerment program based on the “Tibu Bedok” Joint Business Group (KUB) in Cemare Hamlet, Sheet Village, West Lombok is quite successful, it can be seen from the ability of members to meet their daily needs, for shopping and saving for children. schools, for arisan deposits as well as for health purposes and the factors that influence the success of the women's empowerment program through the Joint Business Group (KUB) in Cemare Hamlet, Sheet Village, West Lombok are (a) Environmental factors, (b) Mutual respect between managers and members , (c) Mutual trust between managers and members, and (d) Community participation.